Functional Remodeling of Benign Human Prostatic Tissues In Vivo by Spontaneously Immortalized Progenitor and Intermediate Cells - Jiang, Ming (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Tissue remodeling or regeneration is believed to initiate from multipotent stem and progenitor cells. We report here the establishment of two spontaneously immortalized adult non-tumorigenic human prostate epithelial cell lines, NHPrE1 and BHPrE1. NHPrE1 (CD133(high)/CD44(high)/OCT4(high)/PTEN(high)) was characterized as a putative progenitor cell, and BHPrE1 (p63(high)/p53(high)/p21(WAF1)(high)/RB(high)) was characterized as a putative epithelial intermediate cell. Genomic analysis demonstrated an abnormal karyotype with genomic rearrangements including PTEN amplification in NHPrE1 and CTNNB1 (β-catenin) amplification in BHPrE1 cells. Embedded three-dimensional culture of NHPrE1 showed greater branching than BHPrE1. A tissue recombination-xenografting model was utilized to compare remodeling of human prostatic tissues in vivo. A series of tissue recombinants, made by mixing different ratios of human prostatic epithelial cells and inductive rat urogenital sinus mesenchyme, were grafted to the renal capsule of severe combined immunodeficient mice. Both cell lines were able to regenerate benign secretory ductal-acinar architecture in vivo, containing intact basal and luminal epithelial layers confirmed by the expression of appropriate CK profiles. Prostate-specific antigen, 15-lipoxygenase-2, androgen receptor, and NKX3.1 proteins were appropriately expressed in the regenerated epithelia. Regeneration of benign prostatic glandular structures could be achieved using as few as 10 NHPrE1 cells, whereas 200,000 BHPrE1 cells were required to achieve prostatic architecture. This suggests a greater proportion of progenitor/stem cells in NHPrE1 than in BHPrE1. These cell lines provide important data on progenitor and intermediate cell phenotypes and represent significant new tools for the elucidation of molecular mechanisms of human prostatic regeneration, pathogenesis, and carcinogenesis.